PENDEKATAN CTL DALAM MATERI ENERGI BUNYI DAN SIFATNYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA (PTK PADA SISWA KELAS IV SDN CIPAMEUNGPEUK KECAMATAN SUMEDANG SELATAN KABUPATEN SUMEDANG) - Santi, Dwi Kartika; Panjaitan, Regina Lichteria; Maulana, Maulana (Jurnal Pena Ilmiah, 2017)
CTL approach can improve student learning outcomes, make students more active, creative and enthusiastic in learning, follow the learning activities well and can answer the teacher evaluation questions quickly and accurately. From the data obtained in class IV SDN Cipameungpeuk experiencing problems can be seen from the initial data retrieval obtained by researchers from 24 students who complete the KKM only 5 students. Therefore it needs to be improved from the learning process and learning outcomes. The method used in this research is Classroom Action Research. To declare the data obtained then it needs to be validated. The process in this study was done three cycles to improve it. After making improvements as many as three cycles that the students' learning outcomes increased 50%, 70% to 87%. In this case by applying the CTL approach can obtain significant results.